The Gothic as Camp: Queer Aesthetics in The Monk - Fincher, Max (Romanticism on the Net, 2006)
AbstractThis article investigates how and why the Gothic can be described as camp. Examining the ascription of ‘camp’ by Susan Sontag and others to describe the Gothic, it suggests that the Gothic is camp because it is queer. Moving away from a reading of camp as a style stripped of its queer meanings (in particular the reading of the Gothic as camp because it is ‘theatrical’, ‘hyperbolical’ or ‘artificial’) a reading of camp is offered that uses queer theory which questions the naturality and authenticity of gender. In particular, Fabio Cleto’s idea of how camp represents a crisis of reading the signs of naturality can be applied to the Gothic’s use of the supernatural. The queer valency of Gothic writing, especially in texts such as The Monk, emerges in how the body can be misinterpreted. In The Monk, the voice and the gaze as conduits of desire and phobia are those signifiers of the body that are shown to disturb a sex-gender binary and to provoke a crisis of reading. This anxiety about seeing and understanding desire in not-so-easily visible bodies (like the supernatural) connects to socio-cultural anxieties about how reading gender to read same-sex desire is unstable in the early nineteenth century. An overview of how queer helps us to understand why the Gothic is camp is offered, and then a specific analysis of where the camp effects occur in The Monk is provided through a close reading.